Subacute infective endocarditis due to Lodderomyces elongisporus: a case report and review of the literature - Qiu, Ye; Shi, Yongying; Mai, Ying; Wu, Zhile; Guan, Jing; Huang, Juanni; Su, Danhong; Ye, Feng; Li, Zhengtu (Frontiers in Public Health, 2023)
Lodderomyces elongisporus, a rare emerging pathogen, can cause fungemia often related to immunosuppression or intravenous devices. Herein, we report the case of a 58-year-old woman with subacute infective endocarditis due to Lodderomyces elongisporus identified by blood fungal culture and whole-genome sequencing, who was treated with antifungals, mitral replacement and endocardial vegetation removal surgery.